Loss aversion in the trade-off between wages and commuting distances - Wolfgang Dauth; Peter Haller (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We exploit administrative data on exact commuting distances for a large sample of German employees and study the relation of commuting and wages. We find that it requires 1.5 times as much money in terms of higher wages for job changers to accept an increase of their commute as compared to their willingness to pay for a reduction by the same distance. This provides non-experimental evidence for loss aversion. One third of this can be attributed to sorting of workers into certain firms at various distances and the remainder to a match-specific wage component that workers and firms bargain over.
Keywords: D90; J31; J64; R12; R40; 330; commuting; loss aversion; marginal willingness to pay; job search